MOTIVASI PETANI DALAM BUDIDAYA PADI PULU MANDOTI - Jumarni Latif; Nurbaya Busthanul; A. Amrullah (Hasanuddin University, 2020)
Farmer motivation is defined as a condition that drives a person to carry out an action in order to achieve his goals. Pulu Mandoti is one of the rarest types of fragrant glutinous rice. Pulu Mandoti can only grow in mountainous areas with an altitude of 700 meters above sea level. One of the villages that meets these criteria is Salukanan Village, Baraka sub-District, Enrekang District. This study aims to describe the system of Mandoti Pulu rice cultivation and to determine the motivation of farmers in the cultivation of Mandoti Pulu rice. This research was conducted in Salukanan Village, Baraka Subdistrict, Enrekang District in July 2019 using a descriptive qualitative method, by collecting information through interviews and questionnaires, then the information was processed using a Likert scale, and analyzed descriptively qualitatively. In conclusion, the cultivation conditions of the mandoti rice plant varieties used are local seeds, the process of land management is done by spraying herbicides, planting by way of transplanting with planting spacing, ie spacing of 25x25 cm tiles, fertilizing is done on average 5 times in one run planting season, i.e. before planting, 7 days after planting, 3rd week, 6th week, and 12th week, irrigation using water coming from the mountains using semi-technical irrigation, controlling pests and diseases by spraying appropriate pesticides such as supremo, regent, dangke and rat poison, harvest after rice aged 6-7 months ie in September to November is carried out using a technology that is still simple, ani-ani, post-harvest activities carried out namely drying and threshing. While the motivation of farmers in the cultivation of Pulu Mandoti rice from the aspect of the economic environment is at a moderate level, aspects of the social environment are at a high level, and aspects of the natural environment are at a high level.